Pengembangan Community-Based Tourism Sebagai Strategi Pemberdayaan Ekonomi Masyarakat (Studi Pada Objek Wisata Pantai Leuge Aceh Timur) - Nurwahidah; Muhammad Jamil (Jurnal EMT KITA, 2022)
This study aims to obtain an overview of the utilization of Community-Based Tourism (CBT) ideas in Leuge Beach, East Aceh. namely: (1) knowing the efforts made by the Government of East Aceh in creating a tourism travel industry (CBT) Based on Local Areas, (2) knowing the potential of the travel industry that can be formed into CBT, (3) obtaining data on the inhibiting variables of CBT in the region. East Aceh, and (4) using the CBT progress model as a methodology for regional monetary strengthening in the East Aceh government. The efforts of the East Aceh Regional Government in realizing CBT as one of the regional monetary strengthening techniques are carried out through: (a) a program to increase the destination of the travel industry, (b) an advertising promotion project for the travel industry, and (c) an organizational improvement program. Meanwhile, the types of travel industries that can be formed into regions based on the tourist travel industry in East Aceh include the travel industry, beaches, educational, social, make-up, and culinary industries. travel industry. There are several components that hinder the progress of CBT in the East Aceh Government, namely: (a) the framework has not been enforced, (b) regional investment in creating the travel industry is still low, and (c) the organization has not been fully resolved.